Farmland Preservation and Urban Expansion: Case Study of Southern Ontario, Canada - Caldwell, Wayne; Epp, Sara; Wan, Xiaoyuan; Singer, Rachel; Drake, Emma; Sousa, Emily C. (Frontiers in Sustainable Food Systems, 2022)
Farmland is an essential resource for the sustainability and security of human food systems. Preserving an agricultural land base is critical, as it is significantly affected by local, national and global urbanization. This paper reviews the farmland preservation policy framework within Ontario and provides insight into the role of different levels of government in protecting this critical resource. It also provides data at a regional level that provides the basis to evaluate the success of provincial and local policies. By tracking agricultural land conversion through local Official Plan Amendments, this study documents farmland loss across southern Ontario between 2000-2017 and analyzes the role of provincial policies in preserving farmland in different geographic regions. Data from 36 counties/regions shows that the provincial policies and local planning framework have worked in tandem to significantly affect the agricultural land base in Southern Ontario. In Central Ontario, the most urbanized area of Canada, the Province’s Greenbelt Plan has significantly reduced the rates of farmland loss since 2005, while the Growth Plan and other policies contributed to enhanced municipal control over agricultural land conversion. Specifically, the Inner Ring municipalities have played increasingly active roles in agricultural land protection with both planning approaches and local initiatives. Outer Ring municipalities have seen increasing urbanization pressure. Data on farmland loss for non-agricultural use showed large-scale municipality-led urban boundary expansions and small-scale individual applications on policy changes. In Western Ontario, over the past two decades, there has been no obvious upward or downward trend of farmland loss. Most of the farmland conversion cases in this region were small-scale applications with the purpose of creating small lots on existing agricultural land to allow for non-agricultural uses such as commercial, recreational, residential and agricultural facilities. Since 2000, Eastern Ontario, which has the smallest provincial share of prime agricultural land, has experienced limited farmland loss, consisting mostly of small-scale, individual applications on land use re-designations (partially reflecting reduced acreages of prime agricultural land). The provincial policy impact on farmland preservation is not as obvious in this region.